EFEKTIFITAS PENGARUH ABDOMINAL STREACHING EXERCISE DAN KOMPRES HANGAT TERHADAP INTENSITAS NYERI DISMENORE - Putri, Yelmi Reni; Dewi, Ratna; Yuliani, Yuliani (REAL in Nursing Journal, 2019)
Pain during menstruation causes discomfort in daily physical activity. This complaint related to repeated absences at school or in the workplace. Approximately 70%-90% menstrual pain cases occurred when teens. This report aims to review the effectiveness of influence abdominal streaching exercise and compress warm against intensity of pain dysmenorrhea primer on adolescent girls Secondary Schools Light Islamic Payakumbuh City in 2018. This research using design research design Quasy Experiment Two Group Pre-Post Test Design. The study is done Secondary Schools Light Islamic Payakumbuh in the city February-April 2017 with the total sample 20 people with a dysmenorrhea when menstrual. Engineering the sample conducted using purposive sampling both the questionnaire. Research analysis this is a Univariat and Bivariat. Statistical tests used is Dependent t-test and the Independent t-test with Pvalue = 0,05. The  research  results  obtained  the  average  level  of  pain  dysmenorrhea group abdominal streaching exercise is 3,80 and the average level of pain dysmenorrhea group 3.90 compress warm .On this research there were differences in the average level of pain dysmenorrhea between group abdominal streaching exercise with compress warm with the difference in the average pain and dysmenorrhea 0,100 value Pvalue = 0,791. Based on the above it can be concluded that is the effectiveness of abdominal streaching exercise just before menstruation and the compress warm after menstruation can reduce the pain dysmenorrhea in the abdominal streaching exercise with the compress warm. Hopefully this research able to enhance reference new in reduce pain dysmenorrhea for teens who often find pain on menstruation.